1994
DOI: 10.1243/pime_proc_1994_208_301_02
|View full text |Cite
|
Sign up to set email alerts
|

Improved Trajectory Planning using Arbitrary Power Polynomials

Abstract: Increasing demands for higher operational speeds, the need for flexible machinery and recent developments in microchip technology have made programmable machine systems an attractive alternative to conventional systems. However, some difficulties still remain for proper control of programmable systems, especially at higher speeds. These can be categorized into two groups : trajectory planning and trajectory tracking. Conventional trajectory planning methods are ineffective for general application, especially w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…(2) between the design points and have a tendency to pro-Again, there will be constraints on the maximum velocduce oscillations [23]. For example, Piazzi and Visioli ity, acceleration and displacement that can be imposed showed that it was necessary to switch to another funcby the drive system.…”
Section: Which Is Optimized To Give the Fastest Motion Withinmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) between the design points and have a tendency to pro-Again, there will be constraints on the maximum velocduce oscillations [23]. For example, Piazzi and Visioli ity, acceleration and displacement that can be imposed showed that it was necessary to switch to another funcby the drive system.…”
Section: Which Is Optimized To Give the Fastest Motion Withinmentioning
confidence: 99%
“…t=T S , as suggested in reference [22], in order to obtain a smooth convergence to the end-position. However, The most popular function for trajectory selection is a polynomial function of time [22,23]. The order and the switching is done at t=T S where no errors can be tolerated as the whole purpose of the exercise is to reach coeYcients of the polynomial function can be calculated in order to satisfy the design points de ned in terms of the end-position at T S seconds and stay there without any vibration.…”
Section: Which Is Optimized To Give the Fastest Motion Withinmentioning
confidence: 99%
“…All the trajectories used in this study have been designed by the motion design software called "MOTDES". 36 The robot has three axes, but axes 1 and 2 were used for the implementation of example trajectories in the vertical plane (see Figure 1). The results for revolute and prismatic joints are shown in the first and second column of Figure 4 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…These advantages make the power form of polynomials particularly appropriate for motion design. In spite of these advantages, this function may su er from unexpected oscillations between the boundary conditions at higher degrees and may cause important problems [6 ]. This side e ect may be eliminated by dividing the whole motion into smaller segments and then a number of lower-order polynomials applied to these segments.…”
Section: Motion Designmentioning
confidence: 99%